The Effect of Using Magic Puffer Ball Media on The Creativity of Children 5-6 Years At Private Kindergarten Budi Murni 2 Medan - Daniel Mardongan M Aritonang; Anita Yus (Indonesian Journal of Advanced Research, 2023)
In this study, the problem is that children's creativity has not fully developed as expected. This study aims to determine the effect of using magic puffer ball media on creativity aged 5-6 years at TK Budi Murni 2 Medan. This study uses an approach with an experimental method (Quasi-experiment design) in the form of The Equivalent Time Samples design. The population in this study were all children aged 5-6 years in class B3 with a total sample of 20 children in Kindergarten Budi Murni 2. The study was conducted with 3 treatments. The data collection instrument utilizes the observation sheet. From the data analysis, the data had an average score for treatment 1 of 5.65, then treatment 2 received an average value of 9.6 while the third treatment had an average value of 12.95. Based on data analysis through non-parametric hypothesis testing, the SPSS 23 statistic test value is 0.000. Therefore it can be concluded that the use of magic puffer ball media has a significant influence on the creativity of children aged 5-6 years at Budi Murni 2 Kindergarten.